An Infant Diagnosed With Hydrocephalus by Point-of-Care Ultrasound. Issue 4 (April 2017) - Yaeger, Susan K.; Marin, Jennifer R.
Abstract : Abstract: Point-of-care ultrasound has become a valuable tool for pediatric emergency physicians, with an increasing number of indications being described. In this case presentation, we demonstrate the use of point-of-care ultrasound in the pediatric emergency department to diagnose ventriculomegaly in an infant presenting with a seizure.